PENGARUH KOMPETENSI PROFESIONAL DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PERILAKU KERJA DAN KINERJA GURU BIMBINGAN DAN KONSELING SMA-SMK SE- KABUPATEN LOMBOK UTARA - FATMAWATI FATMAWATI (Master of Management, Mataram University, 2016)
This research is aimed at determining the effect of professional competence and leadership of principal on the work attitude and work performance of teacher of counseling in SMA-SMK in North Lombok. This research is an causal associative study. The data were collected through saturated sample, where the population of the study are all 43 teachers of counseling in SMA/SMK of North Lombok. The data were analyzed with path analysis.The researcg showed that 1) there is a positive and significant effect of professional competence and principal leadership on the performance of teachers of counseling in SMA/SMK of North Lombok, 2). There is a direct, positive and significant effect of professional competence and principal leadership on the performance of teachers of counseling in SMA/SMK of North Lombok, 3). There is an indirect, but positive and significant effect of professional competence and principal leadership on the performance of teachers of counseling in SMA/SMK of North Lombok. Keywords: professional competence, Principal Leadership, Work attitude, Performance